Combined virtual reality and haptic robotics induce space and movement invariant sensorimotor adaptation. (8th January 2021) - Wilf, Meytal; Cerra Cheraka, Mouna; Jeanneret, Max; Ott, Renaud; Perrin, Henri; Crottaz-Herbette, Sonia; Serino, Andrea
Abstract: Prism adaptation is a method for studying visuomotor plasticity in healthy individuals, as well as for rehabilitating patients suffering spatial neglect. We developed a new set-up based on virtual-reality (VR) and haptic-robotics allowing us to induce sensorimotor adaptation and to reproduce the effect of prism adaptation in a more ecologically valid, yet experimentally controlled context. Participants were exposed to an immersive VR environment while controlling a virtual hand via a robotic-haptic device to reach virtual objects. During training, a rotational shift was induced between the position of the participant's real hand and that of the virtual hand in order to trigger sensorimotor recalibration. The use of VR and haptic-robotics allowed us to simulate and test multiple components of sensorimotor adaptation: training either peripersonal or extrapersonal space and testing generalization for the non-trained sector of space, and using active versus robot-guided reaching movements. Results from 60 neurologically intact participants show that participants exposed to the virtual shift were able to quickly adapt their reaching movements to aim correctly at the target objects. When the shift was removed, participants showed a systematic deviation of their movements during open-loop tasks in the direction opposite to that of the shift, which generalized to un-trained portions of space and occurred also when their movements were robotically-guided during the adaptation. Interestingly, follow-up questionnaires revealed that when the adaptation training was robotically-guided, participants were largely unaware of the mismatch between their hand and the virtual hand's position. The stability of the aftereffects, despite the changing experimental parameters, suggests that the induced sensory-motor adaptation does not rely on low-level processing of sensory stimuli during the training, but taps into high-level representations of space. Importantly, the flexibility of the trained space and the option of robotically-guided movements open novel possibilities of fine-tuning the training to patients' level of spatial and motor impairment, thus possibly resulting in a better outcome. Highlights: A new setup for sensorimotor adaptation using virtual reality and haptic robotics. Participants trained in near or far space, with active or robot-guided movements. Aftereffects in open-loop tasks transferred between near and far space. Open-loop aftereffects were evident also following robot-guided adaptation training. This setup can potentially serve as a rehabilitation tool for neglect patients.